1999
DOI: 10.1046/j.1365-2249.1999.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, thyroid hormones and muscle mass influence natural killer (NK) innate immunity in healthy nonagenarians and centenarians

Abstract: Increasing evidence has demonstrated that the immune system closely interacts with other physiological systems, whose communications are mediated by circulating cytokines and hormones. The aim of our study was to test whether the number and cytolytic activity of NK cells in a group of relatively healthy Italian nonagenarians and centenarians were affected by the modifications of endocrine, metabolic and functional parameters that occur during ageing. Because of the extreme age of the study population, a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 51 publications
(47 reference statements)
3
33
0
2
Order By: Relevance
“…59 In these pregnant adolescents, vitamin D sufficiency was associated with lower concentrations of leukotrienes and increased antioxidant and oxidase enzyme concentrations. The association between vitamin D status and a reduced inflammation has been noted in previous metabolomic studies that have identified vitamin D metabolites as potential biomarkers in inflammatory conditions, including asthma, 60 ankylosing spondylitis, 61 and obesity; 62 and is supported by studies highlighting the anti-inflammatory effects of vitamin D. [63][64][65][66] Vitamin D is known to play an extensive role in both innate and adaptive immunity, [67][68][69] but its role in the inflammatory process during pregnancy has not been established. A previous In a recent analysis of maternal vitamin D status and inflammation across adolescent pregnancy from the same cohort (n ¼ 168), Akoh et al found that maternal vitamin D status was correlated with tumor necrosis factor a (TNF-a) and C-reactive protein (CRP); analyses are ongoing to measure inflammatory cytokines (IL-6, IL-10, TNF-a, CRP) in archived maternal and cord serum (Unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…59 In these pregnant adolescents, vitamin D sufficiency was associated with lower concentrations of leukotrienes and increased antioxidant and oxidase enzyme concentrations. The association between vitamin D status and a reduced inflammation has been noted in previous metabolomic studies that have identified vitamin D metabolites as potential biomarkers in inflammatory conditions, including asthma, 60 ankylosing spondylitis, 61 and obesity; 62 and is supported by studies highlighting the anti-inflammatory effects of vitamin D. [63][64][65][66] Vitamin D is known to play an extensive role in both innate and adaptive immunity, [67][68][69] but its role in the inflammatory process during pregnancy has not been established. A previous In a recent analysis of maternal vitamin D status and inflammation across adolescent pregnancy from the same cohort (n ¼ 168), Akoh et al found that maternal vitamin D status was correlated with tumor necrosis factor a (TNF-a) and C-reactive protein (CRP); analyses are ongoing to measure inflammatory cytokines (IL-6, IL-10, TNF-a, CRP) in archived maternal and cord serum (Unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the impaired NK cell cytotoxicity represents a high risk factor for the appearance of infections in advanced age. Studies in nonagenarian/centenarians showed an NK cell cytotoxicity that was similar in old subjects (aged 60-65 years) but higher than that in slightly older subjects (75 -85 years) (Sansoni et al ., 1992;Mariani et al ., 1999;Mocchegiani et al ., 2003). This suggests that preservation of NK cell cytotoxicity in middle age may be a crucial immune function in order to escape some age-related diseases and to reach healthy aging.…”
Section: Nk Cell Function and Agingmentioning
confidence: 99%
“…Findings in centenarian subjects and in very old mice confirm the relevance of zinc in restoring NK cell function in the elderly. Indeed, they have a well-preserved NK cell cytotoxicity, good zinc ion bioavailability and satisfactory IFN-γ production (Miyaji et al ., 2000;Mocchegiani et al ., 2003) as well as preserved thyroid hormone turnover (Mariani et al ., 1999). This last finding also supports, as described above, a sufficient maintenance of the neuroendocrine-immune network, via the zinc pool, in older individuals, contributing to avoidance of some age-related diseases.…”
Section: Nk Cell Function and Agingmentioning
confidence: 99%
“…TH may favorably influence innate immunity and natural killing activity [30][31][32][33]. This is a rapidly expanding field.…”
Section: Reduction Of Inflammationmentioning
confidence: 99%